2006
DOI: 10.1002/eji.200535004
|View full text |Cite
|
Sign up to set email alerts
|

The Rap GTPases mediate CXCL13‐ and sphingosine1‐phosphate‐induced chemotaxis, adhesion, and Pyk2 tyrosine phosphorylation in B lymphocytes

Abstract: The localization of B cells to lymphoid organs where they can become activated and differentiate into antibody-secreting plasma cells is controlled by multiple chemoattractants that promote cell migration and integrin-mediated adhesion. CXCL13 and sphingosine 1-phosphate (S1P) are two important chemoattractants that control the trafficking of B cells. CXCL13 directs B lymphocytes to lymphoid follicles where they receive survival signals and, if activated, undergo a germinal center response. In contrast, S1P al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
50
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 65 publications
0
50
0
Order By: Relevance
“…Phg2 was reported to promote the Rap1-regulated cell adhesion [162], but we have evidence suggesting that Phg2 also regulates the chemoattractant-induced phosphorylation of myosin II (T. Mammalian Rap1 has attracted much attention because of its involvement in several aspects of cell adhesion [161]. However, recent data suggest that chemoattractant-induced Rap1 signalling at the leading edge is critical for lymphocyte polarity and migration [166,167]. Evidence of a role for mammalian Rap1 in cell migration and polarity includes the observations that lymphocytes expressing a constitutively active Rap1 mutant undergo spontaneous polarization and display increased cell migration, in addition to enhanced adhesion [168] and that rap −/− T-cells present polarization defects [169].…”
Section: Regulation Of Actin-myosin Assemblymentioning
confidence: 97%
“…Phg2 was reported to promote the Rap1-regulated cell adhesion [162], but we have evidence suggesting that Phg2 also regulates the chemoattractant-induced phosphorylation of myosin II (T. Mammalian Rap1 has attracted much attention because of its involvement in several aspects of cell adhesion [161]. However, recent data suggest that chemoattractant-induced Rap1 signalling at the leading edge is critical for lymphocyte polarity and migration [166,167]. Evidence of a role for mammalian Rap1 in cell migration and polarity includes the observations that lymphocytes expressing a constitutively active Rap1 mutant undergo spontaneous polarization and display increased cell migration, in addition to enhanced adhesion [168] and that rap −/− T-cells present polarization defects [169].…”
Section: Regulation Of Actin-myosin Assemblymentioning
confidence: 97%
“…Expressing RapGAPII in A20 cells completely blocked activation of Rap1 and Rap2 by CXCL12 (Figure 1b), a chemokine that is produced in the lymphoid organs, bone marrow, liver, lungs and ovaries (Shirozu et al, 1995) and which has a key role in the dissemination of many types of tumors. RapGAPII expression selectively blocks CXCL12-induced Rap activation and does not affect CXCL12-induced activation of Akt/protein kinase B, MAP kinases or the Rac1 GTPase in B-lymphoma cell lines (McLeod et al, 2002;Durand et al, 2006). Moreover, expressing RapGAPII in A20 cells did not alter the levels of Rap1 or Rap2 (Figure 1b), did not reduce cell surface expression of CXCR4 (the receptor for CXCL12), LFA-1 or VLA-4 (Figure 1c), and did not alter the in vitro proliferation of A20 cells (Figure 1d).…”
mentioning
confidence: 98%
“…Activated Rap is a master regulator of cytoskeletal organization and integrin activation (Bos, 2005). In lymphocytes, chemokine receptor signaling leads to Rap activation and this is critical for chemokines to stimulate cell migration and integrin-mediated adhesion (McLeod et al, 2002(McLeod et al, , 2004Shimonaka et al, 2003;Durand et al, 2006). However, the role of Rap activation in the in vivo dissemination and establishment of B-cell lymphomas is not known.…”
mentioning
confidence: 99%
“…B cells circulate continuously throughout the body via the blood and (S1P) receptors to stimulate B-cell migration and adhesion. 12,14 Rap activation is also important for receptorinduced actin polymerization, cell spreading and cytoskeletal reorganization in both primary B cells and B-lymphoma cells. 15 These findings suggested that Rap activation might be essential for the in vivo metastatic spread of B-cell lymphomas.…”
mentioning
confidence: 99%
“…In both normal B cells and B-lymphoma cell lines, signaling via chemoattractant receptors, the BCR and integrins all activate Rap. [11][12][13] Moreover, we have shown that chemokineinduced Rap activation is essential for the chemoattractants CXCL12 (SDF-1), CXCL13 and sphingosine-1-phosphate lymphatic systems. The extravasation of B cells out of the blood and into tissues is a multi-step process that requires selectinmediated rolling on the surface of vascular endothelial cells, intergin-mediated firm adhesion to the endothelial cells, and migration across the endothelial cell monolayer that makes up the vessel wall (Fig.…”
mentioning
confidence: 99%